Antimicrobial effects of chitosan and essential oils on postharvest diseases of pomegranate fruit - Munhuweyi, Karen (Stellenbosch : Stellenbosch University, 2017)
Thesis (PhDFoodSc)--Stellenbosch University, 2017.